Implementasi Kebijakan Kampus Merdeka sebagai Strategi Pemerintah dalam Menanggapi Tantangan Pendidikan di Masa Pandemi - Tedi Tedi; Amir Mirdad; Toha Suryana; Muhamad Rafli; Wahid Nurwaluyadin Sofyan (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to analyze the implementation of the Kampus Merdeka policy as a government strategy in addressing the challenges of higher education during the pandemic. The background of this research focuses on the importance of innovation in an educational system that is adaptable to crisis conditions, such as the COVID-19 pandemic, which demands flexibility in teaching and learning processes as well as the empowerment of students to become more independent. The objective of this study is to examine how the Kampus Merdeka policy is implemented in universities and its impact on the quality of learning, student autonomy, and their preparedness for the workforce. This research employs a qualitative approach with a case study design, involving data collection through in-depth interviews, observations, and analysis of policy-related documents. The findings reveal that the implementation of Kampus Merdeka during the pandemic has encouraged increased student creativity, interdisciplinary collaboration, and more contextual learning experiences beyond the classroom. The policy also provides opportunities for students to develop their potential in a more flexible and adaptive manner. This study concludes that Kampus Merdeka, as a government policy, holds significant potential in shaping a higher education system that is more relevant and resilient to changing times, particularly in the context of a global crisis.